Anthropology of transformation: from Europe to Asia and back : essays in honour of Professor Chris Hann - Buzalka, Juraj; Pasieka, Agnieszka; Hann, Chris (Open Book Publishers, 2022)
This collection of essays is the result of the joint efforts of colleagues and students of the leading social anthropology and post-socialism theorist, Professor Chris Hann. With the thirtieth anniversary of the collapse of the Berlin Wall in 2019 as their catalyst, the authors reflect upon Chris Hann’s lifelong fieldwork in the discipline, spanning regions as diverse as East Central Europe, Turkey, and the Chinese north-west. The collapse of the Berlin Wall naturally triggered a plethora of analysis and scholarly research. Sociocultural anthropology, with its focus on ethnographic study and on the gradual evolution of social relations, sharply contrasted with the emphasis on dramatic rupture brought about by the 1989 transition. Continuing in this tradition, this volume, through micro-level analysis of societal transformation from the post-war years to the present day, provides an alternative perspective to the neoliberalist views often encountered in the scholarship on political and economic modernisation. The more nuanced analysis of social transformations proposed here is a particularly useful tool in the investigation of contemporary issues such as the COVID-19 pandemic, the refugee ‘crisis’, and the rise of right-wing populism in Eastern Europe and elsewhere. Anthropology of Transformation will be of interest to researchers in the fields of socio-cultural anthropology, religion and economics. Moreover, the book’s discussion of issues widely discussed beyond the field of academia such as neoliberalism and the welfare state, and populist and exclusionary politics, will appeal to non-specialist readers.